Nitrite Triggers Reprogramming of the Oral Polymicrobial Metabolome by a Commensal Streptococcus - Huffines, Joshua T.; Stoner, Sara N.; Baty, Joshua J.; Scoffield, Jessica A. (Frontiers in Cellular and Infection Microbiology, 2022)
Commensal streptococci regulate health and homeostasis within oral polymicrobial communities. Interestingly, high salivary nitrite concentrations have been associated with improved health in the oral cavity. We have previously demonstrated that nitrite assists hydrogen peroxide-producing oral commensal streptococci in regulating homeostasis via the generation of reactive nitrogen species (RNS), which have antimicrobial activity on oral pathogens. However, it is unknown how nitrite and commensal streptococci influence the metabolome of oral polymicrobial communities. In this study, we report that nitrite aids commensal streptococci in the inhibition of multi-kingdom oral pathogens that reside in distinct oral niches, which supports commensal dominance. More importantly, we show that commensal streptococci utilize nitrite to drive the metabolic signature of multispecies biofilms in a manner that supports commensal metabolism and resistance to RNS, and restricts metabolic processes that are required for pathogen virulence. Taken together, our study highlights how commensal streptococci use nitrite to trigger shifts in the oral polymicrobial metabolome to support health and homeostasis.